Physiohappy interface in the treatment of wrist and hand of a child with cerebral palsy: case repot (Research, Society and Development, 2020)
The aim of the study was to verify the applicability of virtual reality (VR) using the low-cost PhysioHappy interface, associated to conventional physical therapy in the rehabilitation of wrist and hand of individuals with unilateral spastic Cerebral Palsy (CP). This is a case report that describes the rehabilitation of a 12-year-old girl with unilateral right spastic CP who underwent a 12-session treatment with conventional physiotherapy and the PhysioHappy interface. It was found that the child improved manual dexterity in the Box and Block test and the muscular activation of wrist and hand extensors and flexors measured through electromyography. It was concluded that the interface used associated with conventional physiotherapy can be considered as the treatment of a child with spastic Cerebral Palsy, expanding the existing therapeutic strategies.